Correlation between smartphone addiction and psychosocial factors among students and assessment of fMRI brain activation in response to reward - Nisha, Syed Nasser (2019)
Smartphone-based Instagram addiction is an emerging digital addiction and is of mental, physical and social concern among the young university students. Functional magnetic resonance imaging (fMRI) is a non-invasive neuroimaging technique that utilises Blood Oxygen Level Dependent imaging to determine the hemodynamic response function during brain activation in response to a task. This study aimed to identify the socio-demographic distribution of smartphone addiction (SPA) among undergraduate students in Universiti Putra Malaysia (UPM). With the increase in the number of Instagram users in Malaysia, it is important to study the neurobiological mechanism underlying pathological Instagram use (PIGU). This study will provide the first worldwide empirical data regarding the assessment of cue-induced brain activation in ‘Response to Reward’ condition among smartphone-addicted PIGU individuals using validated emotional cues in a task-based fMRI study. In Phase1 study, a cross-sectional study was conducted among 1060 undergraduate students in UPM using validated smartphone addiction scale-Malay version, and Depression, Anxiety, Stress scale to determine the socio-demographic distribution and mental wellbeing. In Phase 2 study, a case-control study using fMRI as a non-invasive biomarker was conducted to identify the regional brain activation in the mesocorticolimbic system during a cue-induced reactivity task among the randomly selected cohort of subjects (addicted n=15, control n=15). This study detected problematic smartphone usage among 60.7% of young undergraduate students in UPM and PIGU was significantly correlated with psychosocial problems (p<0.05). Left Precuneus was significantly activated in the addicted group (pFWE<0.05) and the percentage signal change in right medial prefrontal cortex and right anterior cingulate cortex were significantly correlated with addiction (p<0.05). fMRI is able to non-invasively identify the regions of brain activation in response to the addictive stimulus in the reward system and this study is able to achieve a milestone by providing evidence to support the theories of development of ‘tolerance’ among the SPA individuals.